1977
DOI: 10.1002/jcp.1040900209
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of inhibitors of cell division upon the growth stimulating activities of insulin and serum in nutritionally depleted human and mouse cells

Abstract: Cultured mouse and human cells were arrested in their growth by artificially depriving them of phosphate. The quiescent cells could be stimulated to synthesize DNA and to divide by addition to the growth medium of insulin, dialyzed serum and/or the full concentration of phosphate. In order to gain insight into mechanisms by which insulin and serum stimulate growth, the inhibitory effects of antimitotic agents were examined. Of the inhibitors tested, vinblastine and cytocalasin B abolished the growth promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, cells in some systems are prevented from entering S-phase. This has been shown in rat liver cells after partial hepatectomy (Luyckx and Van Lancker, 1966;Walker et al, 1977) and in serum-stimulated W138 human, C3H and 3T3 mouse, and chick embryo fibroblasts in vitro (Walker et al, 1977;McClain et al, 1977;Kamely, 1977). Lectininduced lymphocyte mitogenesis is also inhibited (Edelman et al, 1973).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, cells in some systems are prevented from entering S-phase. This has been shown in rat liver cells after partial hepatectomy (Luyckx and Van Lancker, 1966;Walker et al, 1977) and in serum-stimulated W138 human, C3H and 3T3 mouse, and chick embryo fibroblasts in vitro (Walker et al, 1977;McClain et al, 1977;Kamely, 1977). Lectininduced lymphocyte mitogenesis is also inhibited (Edelman et al, 1973).…”
Section: Discussionmentioning
confidence: 77%
“…It has also been shown that 3T3 cells can be stimulated to proliferate by insulin if the culture medium is depleted of essential nutrients. This would suggest that the mitogenic action of insulin in this case could be due to the accelerated intracellular transport of some rate-limiting nutrients (23,24) . It follows, therefore, that differentiated PC 13 cells may have specific nutrient requirements for proliferation that can be supplied by insulin-stimulated transport processes .…”
Section: Insulin Effects On Cell Proliferationmentioning
confidence: 93%